FENOMENA UJARAN TEKS DISKRIMINATIF: KOS INI HANYA MENERIMA MAHASISWA MUSLIM DALAM TERANG FILSAFAT RELASIONALITAS DALAM BERAGAMA ARMADA RIYANTO - Yuliana Jaimut; Siklus Rikardus Depa; Eugenius Ervan Sardono (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2022)
This paper is a critical analysis of the text that reads: "This boarding house only accepts Muslim students" based on the philosophy of relationality of Armada Riyanto towards the phenomenon of religious pluralism in Indonesia. Indonesia has various religions. Religious diversity in Fleet Relational Philosophy means acceptance of others in their plurality. The methodology used in this research is Phenomenological Description Analysis (FDA), which examines the text: "This boarding house only accepts Muslim students" in Armstrong's compassionate perspective. The findings of this study are: (1) me and the text. Humans criticize the discriminatory text "this boarding school only accepts students" from the idea of Riyanto's Fleet Relationality. (2) Me and Liyan. Build empathy and dialogue as a 'door' of tolerance. (3) Me and God. Strong faith will further encourage tolerance, not the other way around.